Ethnoveterinary treatments for common cattle diseases in four districts of the Southern Province, Zambia - Michelo Syakalima; Martin Simuunza; Victor Chisha Zulu (Veterinary World, 2018)
Aim: Ethnoveterinary knowledge has rarely been recorded, and no or limited effort has been made to exploit this knowledge despite its widespread use in Zambia. This study documented the types of plants used to treat important animal diseases in rural Zambia as a way of initiating their sustained documentation and scientific validation.